Effect of sulphur rates and sources on yield and mineral composition of white clover - Moreira, Adônis; Evangelista, Antônio Ricardo; Carvalho, Janice Guedes de (Pesquisa Agropecuaria Brasileira, 1998)
The sulphur effect on yield and mineral composition of white clover was studied under greenhouse conditions in plastic pots of 1.5 liter capacity, using a dystrophic dark red latosol (Oxisol) of "cerrado". The experimental design was completely randomized in a factorial scheme (4 x 3), with five replicates. Four rates of CaSO4.2H2O (0, 25, 50 and 100 mg kg-1 of S) and one rate of K2SO4 (50 mg kg-1 of S), in three cuttings were studied. The variables analyzed were: dry matter production (DM), amounts of crude protein (CP), P, K, Ca, Mg and S in the aerial dry matter. The highest DM yield was observed with the application of 100 mg kg-1 of S and the lowest was the one that did not receive S. The S sources did not affect yield. The last cutting showed the lowest yield, probably due to the nutrient depletion. The levels of CP, Ca and S raised with sulphur application and diminished in the last cutting. The levels of P, K and Mg varied according to the cutting number.